2020
DOI: 10.1186/s13046-020-01685-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracelluar matrix in osteosarcoma progression and metastasis

Abstract: Osteosarcoma (OS) is the most common primary bone malignancy and responsible for considerable morbidity and mortality due to its high rates of pulmonary metastasis. Although neoadjuvant chemotherapy has improved 5-year survival rates for patients with localized OS from 20% to over 65%, outcomes for those with metastasis remain dismal. In addition, therapeutic regimens have not significantly improved patient outcomes over the past four decades, and metastases remains a primary cause of death and obstacle in cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 140 publications
3
101
1
Order By: Relevance
“…Adjuvant chemotherapy has been demonstrated to greatly improve the prognosis for patients with osteosarcoma by increasing the five-year survival rate from 20% to approximately 55–70% [ 2 ]. However, the five-year survival rate remains dismal at less than 20% in patients with osteosarcoma and metastatic lesions [ 3 ]. Therefore, the development of novel treatment strategies that target and prevent metastasis is urgently required to promote patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant chemotherapy has been demonstrated to greatly improve the prognosis for patients with osteosarcoma by increasing the five-year survival rate from 20% to approximately 55–70% [ 2 ]. However, the five-year survival rate remains dismal at less than 20% in patients with osteosarcoma and metastatic lesions [ 3 ]. Therefore, the development of novel treatment strategies that target and prevent metastasis is urgently required to promote patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that CTAB significantly inhibits the proliferation of osteosarcoma cells, leading to G1 arrest, suppresses metastasis and induces apoptosis. One of the clinical features of osteosarcoma is the tendency to form metastatic lesions, and the degradation of extracellular matrix is an essential step in cancer invasion and metastasis (22,23). Previous findings have showed that CTAB can selectively inhibit the proliferation of prostate cancer cells and markedly decrease the invasion of DU-145 cells in the collagen matrix (24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that extracellular matrix remodeling is the hallmark of tumor progression. 43 Its transition promotes tumor metastasis but also acts as a physical barrier to inhibit immune cell infiltration. 44 In addition, collagen, the major component of the extracellular matrix, can induce exhaustion of CD8 T cells.…”
Section: Discussionmentioning
confidence: 99%